Pengaruh Lingkungan Akademik Sekolah Terhadap Hasil Belajar Bahasa Arab Siswa Kelas VIII MTsS Miftahussalam Karawaci - Fadilah, Izzah Pudji (INTIFA: Journal of Education and Language, 2024)
Abstract Learning outcomes represent students achievements in the learning process, which can be influenced by external factors. One such factor is the school’s academic environment. A good and conducive academic environment can enhance students learning outcomes. This study aims to determine the effect of the school’s academic environment on students learning outcomes. This research employed a quantitative approach using a survey method with questionnaires. The population consisted of all eighth grade students of MTsS Miftahussalam Karawaci, totaling 33 students. The entire population was used as the sample through a saturated sampling technique. The results of data analysis show that the school’s academic environment has a significant effect on students learning outcomes. This is evidence by the T-value of 4.338, which is greater than the T-table value of 2.040. the school’s academic environment contributed 37,8% to students learning outcomes. Therefore, the hypothesis stating that there is a significant influence of the school’s academic environment on students learning outcomes is accepted. Abstrak Hasil belajar merupakan pencapaian siswa dalam proses pembelajaran yang dapat dipengaruhi oleh faktor eksternal, Salah satunya adalah lingkungan akademik sekolah. Lingkungan akademik yang baik dan kondusif mampu meningkatan hasilbelajar siswa. Penelitian ini bertujuan untuk mengetahui pengaruh lingkungan akademik sekolah terhadap hasil belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui angket. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII MTsS Miftahussalam Karawaci sebanyak 33 siswa. Seluruh populasi dijadikan sampel dengan menggunakan teknik sampling jenuh. Hasil analisis data menunjukkan bahwalingkungan akademik sekolah berpengaruh signifikan terhadap hasil belajar siswa. Hal ini dibuktikan melalui nilai Thitung sebesar 4,338 yang lebih besar dari nilai Ttabel sebesar 2,040.besarnya pengaruh lingkungan akademik sekolah terhadap hasil belajar siswa adalah sebesar 37,8%. Dengan demikian hipotesisyang menyatakan terdapat pengaruh signifikan antara lingkungan akademik sekolah terhadap hasil belajar siswa dapat diterima.